On the Edge of Discourse. Beyond the Differentiation of Discursive and Non-discursive Practices - Wrana, Daniel; Langer, Antje (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
If there were a pop quiz by and for discourse analysts, then it would probably begin with the question: What is a "non-discursive practice"? The question marks the edge of discourse, so to speak; the term alone leads us to assume that "non-discursive practices" are, precisely, no longer discourse. In the following we will discuss this problem of the non-discursive and the various ways of thinking about this edge, this border—whether to walk the fine line or avoid it. First, we shall do so based on theoretical-methodological debates and then, based on several concrete interpretations of texts and observations from various empirical research projects. In this way, we shall orient our work around the conceivable borders of discourse—power, everyday practice, the body, the subject—and develop the thesis that the differentiation of the discursive and the non-discursive is not at all valuable in terms of adding clarity to the debate.URN: urn:nbn:de:0114-fqs0702206